Market Conduct of the Corn Seed Producers: Multinationals Versus Local Companies - Sayaka, Bambang (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2005)
IndonesianSekarang semakin banyak petani jagung yang menggunakan varietas yang produktivitasnya tinggi baik komposit maupun hibrida. Kecenderungan ini mendorong produsen benih untuk mengintensifkan bisnis mereka dengan berbagai strategi. Penelitian ini bertujuan untuk menganalisa strategi pasar yang dilakukan oleh produsen benih jagung di Jawa Timur. Dengan modal, teknologi dan sumberdaya manusia yang lebih baik, perusahaan multinasional cenderung oligopolistik dan mendominasi industri benih jagung. Perusahaan multinasional juga lebih banyak melakukan penjualan melalui pasar terbuka dan memiliki indeks integrasi lebih tinggi. Pemerintah harus melakukan pengawasan yang ketat dalam industri ini agar kepentingan petani tidak dikorbankan. Untuk bersaing dengan perusahan multinasional, perusahaan lokal harus menerapkan strategi pasar yang lebih baik, misalnya meningkatkan kualitas benih dan mengurangi ketergantungan penjualan terhadap proyek pemerintah.EnglishCurrently corn farmers tend to apply high yielding varieties of composite and hybrid types. This trend encourages the corn seed producers to intensify their business, but tight competion has forced them to set their own strategy in order to get market shares. This study aimed at analyzing market conduct carried out by the corn seed producers in East Java. Having stronger capital, technology, and human resources, the multinational producers tended to be oligopolistic and dominated the corn seed industry. The multinationals were better off in selling their products through open market and had higher integration indexes. The government has to strictly apply the existing policy related to this industry’ conduct in order to protect farmers’ interest that may be negated by the competing corn seed producers. To contest with the multinationals, the local producers have to apply better market conduct, for example improving corn seed products and lessening reliance on captive market.